Running the war in Iraq an Australian general, 300,000 troops, the bloodiest conflict of our time - Molan, Jim (HarperCollins, 2008)
Jim Molan is the Australian General who served in Iraq with the Coalition during 2004-05. Initially, under General Ricardo Sanchez, he worked on infrastructure: trying to restore/maintain the provision of water, power and rail services. Under General George W. Casey, he became Deputy Chief of Staff for Strategic Operations with the Multi National Forces Iraq and ran the operations for all the US and Coalition forces assigned to the Iraqi area of operations. He had to interact with the new interim Iraqi government, bringing the political, diplomatic, information, economic and reconstruction sectors into line with the military side. In this book he describes his background and military career, but focuses on describing key aspects of his time in Iraq.